Translation, validation and cultural adaptation of “The Eustachian Tube Dysfunction Questionnaire-7” (ETDQ-7) to Brazilian Portuguese (BR) - Fernanda Pires Gallardo; Ektor Tsuneo Onishi; Francisco Iure Lira; Flávia Barros Suzuki; José Ricardo Gurgel Testa (Brazilian Journal of Otorhinolaryngology, 2019)
Introduction: Chronic Eustachian tube dysfunction can cause several symptoms and middle ear conditions that can impact patient quality of life. It is estimated to be relatively frequent, affecting approximately 5% of adults. The diagnostic tools for this condition are still inadequate. In 2012, McCoul et al. published a questionnaire for the evaluation of Eustachian tube dysfunction named ETDQ-7. They established its replicability and validity. The cutoff point for the diagnosis of chronic Eustachian tube dysfunction was equal to or greater than 14.5, with 100% sensitivity and 100% specificity. Objective: To translate, adapt and validate the ETDQ-7 questionnaire to Brazilian Portuguese. Methods: We translated the questionnaire into Brazilian Portuguese and applied it to 50 patients, 20 of whom had chronic Eustachian tube dysfunction, and 30 controls. Results: The results obtained with the North-American questionnaire were confirmed in its Brazilian version. The cut-off point for the diagnosis of chronic Eustachian tube dysfunction was ≥14, also exhibiting high sensitivity and specificity, very similar to that of ETDQ-7. Conclusion: It is recommended that ETDQ-7 be used to complement the clinical history of patients with chronic Eustachian tube dysfunction; it can also be used as an important tool for diagnosis, patient follow-up and treatment management. Resumo: Introdução: A disfunção crônica da tuba auditiva pode causar diversos sintomas e doenças de orelha média e impactar a qualidade de vida dos pacientes. Estima-se que é uma morbidade relativamente frequente, acomete cerca de 5% dos adultos. Os instrumentos diagnósticos para essa afecção ainda são insuficientes. Em 2012 McCoul et al. publicaram um questionário para a avaliação da disfunção da tuba auditiva denominado ETDQ-7. Eles demonstraram sua reprodutibilidade e validade. O ponto de corte para o diagnóstico de disfunção de crônica da tuba auditiva foi de maior ou igual a 14,5 com 100% de sensibilidade e 100% de especificidade. Objetivo: Traduzir, adaptar e validar o questionário ETDQ-7 para o português brasileiro. Método: Traduzimos o questionário para o português do Brasil e o aplicamos em 50 pacientes, 20 com disfunção crônica da tuba auditiva e 30 controles. Resultados: Os resultados obtidos no questionário americano foram confirmados na versão brasileira. O ponto de corte para o diagnóstico de disfunção crônica da tuba auditiva foi maior ou igual a 14, também com alta sensibilidade e especificidade, muito semelhante ao ETDQ-7. Conclusão: Recomenda-se que o ETDQ-7 seja usado como um complemento na história clínica do paciente com disfunção crônica da tuba auditiva e pode ser usado também como uma importante ferramenta para fins de diagnóstico, seguimento de pacientes e manejos no tratamento. Keywords: Eustachian tube/pathophysiology, Otitis media/diagnosis, Surveys and questionnaires, Translation, Eustachian tube/therapy, Palavras-chave: Tuba auditiva/fisiopatologia, Otite média/diagnóstico, Inquéritos e questionários, Tradução, Tuba auditiva/terapia